Leadership Theory in Digital Era: A Preliminary Investigation to Leadership in the Digital Startup - hendrasto, nur (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
The digital transformation has been a significant discussion since scientists predicted the birth of the digital era. The transformation affects many things, especially in the leadership concept. This article aims at investigating the development of academic literature on leadership in the digital era. We use bibliometric analysis and literature review to give further suggestions on which topics on leadership for a digital startup shall go to the fore. This study has mapped out the academic literature on the keyword "digital leadership" from the early year of the rise of the digital era in 2000, up until the end of 2018. This study shows that the topics related to digital leadership are digital transformation, internet, system, and organization. Between these four topics, the closest relation found in the topics of organization. Therefore to have a better understanding of leadership for the digital startup, further research should target the area of the organization.